Comment on “Medial epicondyle avulsion after elbow dislocation in an adolescent non-professional soccer player treated with a cannulated screw: a case report.” - Rehm, Andreas; Thahir, Azeem; Ngu, Albert (Acta Biomedica Atenei Parmensis, 2021)
.